Examining the Distribution and Recurrence of Referred Pain in Hip Disorders in Children - Siraj Nabi, Tauqeer Nawaz Khan, Tauseef Raza, Akkad Rafiq, Osama Bin Zia, Rakhshinda Younus, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim of current study was to compare the locations and frequency of referred pain in pediatric hip disorders. Methods: Total 85 patients diagnosed with SCFE, LCPD, or TSH were presented in this study. Data on the location of pain was gathered at the initial examination and compared across all disorders. SPSS 22.0 was used to analyze data. Results: There were total 48 (56.5%) males and 37 (43.5%) females among all cases. Mean age of the presented cases was 10.4±8.63 years. 27 cases had SCFE, 25 cases had LCPD and 33 cases had TSH. Among 27 cases of SCFE, 13 cases had hip pain, 7 cases had knee pain 7 cases had thigh pain, in 25 cases of LCPD, 10 cases had hip pain, 6 cases had knee and 9 cases had thigh pain. Among 33 cases of TSH, 12 cases had hip pain, 9 cases had knee and thigh pain was observed in 14 cases. Conclusion: Patients with SCFE, LCPD, and TSH (a pediatric hip condition) had their pain areas compared. Some kids, following adult reports, experienced referred pain in the knees or thighs as a result of hip joint illness. Keywords: Hip disorders, Pain, Location.